Training of the practicing teacher through the Lesson Study: concerns in a complex reality (Praxis Educativa, 2022)
This article responds to a progress of the doctoral research developed in the Basic Education career, distance modality of the Plan for Teacher Professionalization of the Universidad Nacional de Educación-UNAE-Ecuador. It aims to identify the concerns presented by teachers in the context of virtual education through the development of the Lesson Study methodology, specifically in the problematization phase. For this purpose, from a qualitative approach and case study, said concerns expressed in individual interviews, group discussion and written texts are analyzed. Concerns can be observed regarding the dimensions of practical knowledge: knowledge, skills, emotions, values and attitudes. This leads to understanding that the teaching role currently faces new challenges and uncertain realities, concluding on the importance of ongoing training that involves the aforementioned dimensions to investigate and act on and on specific needs.
Keywords: teacher training; pedagogical practice; teacher competencies; teacher effectiveness; complexity